Evolving design : the collection of the best evolving architecture works & projects - Jeong, Ji-seong. (Seoul : CA Press, 2011)
The development of architecture in terms of social, cultural and technical progress has at its center the question of sustainability through which relations between architecture and people can evolve. These titles focus on the building design of 65 projects in the context of urban planning in a single city. It explores the value of effective management information and integration across the entire construction process in the pursuit of a sustainable future.
Includes index.
Text is in English and Korean.
Keywords: Architecture, Modern -- 21st century; Architecture, Modern -- 20th century